2021
DOI: 10.1111/cdev.13496
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure, Family Instability, and Child Psychological Well‐Being in the Context of Migration: Evidence From Sequence Analysis in China

Abstract: This study conceptualizes parental migration as a dynamic family process that exposes children to parental absence and family instability. Using detailed migration histories, this study identifies the left‐behind trajectories of rural Chinese children throughout childhood (age 1–12) and examines the impact on psychological well‐being (N = 3,961). Results indicate heterogeneity in children’s experience of parental migration, which is characterized by both persistence (prolonged parental absence) and instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 94 publications
(103 reference statements)
1
26
0
1
Order By: Relevance
“…With the rapid social and economic development, there has been continued growth of rural-to-urban migration in China over the past 30 years ( 1 ). This phenomenon has been considered as the largest migration in human history ( 2 ), where more than 172 million rural people have migrated from their hometowns to cities for better employment opportunities ( 3 ). As a result, a great number of Chinese rural children have experienced parental migration during their childhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid social and economic development, there has been continued growth of rural-to-urban migration in China over the past 30 years ( 1 ). This phenomenon has been considered as the largest migration in human history ( 2 ), where more than 172 million rural people have migrated from their hometowns to cities for better employment opportunities ( 3 ). As a result, a great number of Chinese rural children have experienced parental migration during their childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Some children even have mixed experiences of being left-behind and being migrants at different times. Literature has focused on the fluidity and heterogeneity of children's migrant experiences ( 3 ). Because of the Hukou , the Chinese Household Registration System determining the distribution of social welfare resources including employment opportunities, medical care, and education resources ( 14 , 15 ), many school-aged MC are limited to access public schools or social welfare.…”
Section: Introductionmentioning
confidence: 99%
“…The separation between parents and children could broadly affect their family structure, child-caring arrangements, and parent-child relationships (38). This also accounted for how migrant parents influenced a broad range of health outcomes among LBC (39,40). As empirical evidence has long acknowledged, we suggested that the parental migration affected BLBC's mental health extensively, accounting for both internalizing (emotional symptoms) and externalizing problems (conduct problems and hyperactivity) (16,41).…”
Section: Discussionmentioning
confidence: 82%
“…Adding weight to the earlier study (21), we suggested that the adverse influence of parental migration on mental health and behavioral aspects might remain constant for PLBC regardless of no longer being left behind. For these children, aside from the experience of separation from parent(s), there existed a new challenge of readapting changes of caregivers and family structure, which might also pose troubles (39). The findings also gave impetus for a longitudinal study to confirm and for future research to distinguish between PLBC (previous MLBC, FLBC, and BLBC) for further insights into the difference in parental roles.…”
Section: Discussionmentioning
confidence: 99%
“…Grandparents as primary caregivers, compared with parental care, were more likely to face financial strain and health issues but less supportive resources, and these factors subsequently decreased the quality of care provided by grandparents (Martin & Zulaika, 2016). Furthermore, children left behind by both parents tended to experience family instability, which increased their risk of poor mental health (Lu et al, 2021). Other scholars argued that left‐behind children might normalize the family structure growing up without parental care in a context where kinship fostering is commonly practiced (Mazzucato, 2015; Ren & Treiman, 2013).…”
Section: Introductionmentioning
confidence: 99%